Logical foundations of computer science : International Symposium, LFCS 2018, Deerfield Beach, FL, USA, January 8-11, 2018, Proceedings /: International Symposium, LFCS 2018, Deerfield Beach, FL, USA, January 8-11, 2018, Proceedings. (2017) - Unknown
No abstract available